488PRandomized trial of prophylactic minocycline for erlotinib-associated skin rash in non-small cell lung cancer (PEARL trial). (24th November 2019) - Kusaka, K; Tamura, A; Kozuki, T; Koreeda, Y; Kita, T; Endo, T; Shibayama, T; Hatakeyama, N; Miura, M; Yamashita, N; Takenoyama, M
Abstract: Background: Acneiform rash as an adverse event often affects the treatment by EGFR-TKIs. Since minocycline has been suggested to reduce the rash, we assessed the efficacy and safety of prophylactic administration of minocycline simultaneously during erlotinib treatment. Methods: Patients of ECOG performance status 0-2 with advanced NSCLC, who had not been treated with EGFR-TKIs and would receive erlotinib treatment were randomized 1:1 into either group A, with minocycline or group B, without minocycline. The patients assigned to group A were started on minocycline 100mg/day orally for 8 weeks with erlotinib. Primary end point was the frequency of grade ≥2 rash acneiform by independent assessment in first 8 weeks. We expected the prophylactic minocycline decreased the incidence of grade ≥2 skin rash from 50% to 30%. The planned sample size was 280 patients with a = 0.025 (one-sided) and b = 0.10. Results: Patients accrual was started in March 2015 and ended in June 2018 because of slow accrual. Ninety-four patients were finally enrolled and 93 were full-analysis set. The median age of the patients was 71 years old (range 45 to 89), 58 patients were female. EGFR mutation status positive/negative/unknown=78/13/2 patients. The frequency of grade ≥2 rash acneiformby independent assessment was 33.3% [95%C.I. 20.0-49.0%] in group A vs. 44.2% [95%C.I. 29.1-60.1%] in group B (p = 0.296). The frequency by physicians' evaluation was 31.3% [95%C.I. 18.7-48.8%] and 45.5% [95%C.I. 30.4-61.2%] (p = 0.161). However, the frequency of grade ≥2 rash acneiform on day 15 by physicians' evaluation was significantly decreased (4.4% [95%C.I. 5.3-14.8%] in group A vs. 25.0% [95%C.I. 13.2-40.3%] in group B (p = 0.005)). As for toxicity, the incidence of any grade skin-related toxicity as pruritus (39.6% vs. 63.6%) and pain of skin (14.6% vs. 25.0%) was less common in group A. Hence, anorexia (41.7% vs 20.5%), nausea (25.0% vs 4.5%), and dysgeusia (22.9% vs 15.9%) occurred more frequently. Conclusions: Although the frequency of acneiform rash tended to decrease, prophylactic administration of minocycline is not recommended because of increasing gastrointestinal toxicity. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: T. Kozuki: Honoraria (self), Research grant / Funding (self): AstraZeneca; Honoraria (self), Research grant / Funding (self): Chugai Pharmaceutical Co.; Honoraria (self), Research grant / Funding (self): Eli-Lilly Japan; Honoraria (self): Taiho Pharmaceutical Co.; Honoraria (self): Ono Pharmaceutical Co.; Honoraria (self): Bristol-Myers Squibb; Honoraria (self), Research grant / Funding (self): MSD; Honoraria (self): Boehringer Ingelheim; Honoraria (self): Kyowa-Hakko Kirin; Honoraria (self): Pfizer; Honoraria (self): Nippon-kayaku; Research grant / Funding (self): Merck Biopharma. M. Takenoyama: Honoraria (self), Research grant / Funding (self): Chugai Pharmaceutical. All other authors have declared no conflicts of interest.